Pengaruh Dimensi Budaya Hofstede Terhadap Deviant Workplace Behavior. Studi Pada Karyawan Kantor Pelayanan Pajak Pratama Singosari - Himmah, Dewi Faikhotul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to determine the effect of Hoftede cultural dimensions simultaneously or partially on deviant workplace behavior to Pratama Singosari Tax Office’s employees . This type of research used in this research is explanatory research to study the effect of independent variables, namely power distance, collectivism/individualsm, masculinity/feminimity, uncertainty avoidance and the dependent variable is workpace deviant behavior. The research instrument used was a questionnaire. Data analysis tool used in this study is a multiple linear regression, which includes the classic assumption test, multicollinearity test, normality test, and heterokedastisitas test. As for testing the hypothesis include the F test and t test. Results showed variable power distance, collectivism /individualsm, masculinity/feminimity, partially contained is not significant influence on the workpace deviant behavior. As for the variable uncertainty avoidance partially contained significant influence on deviant behavior workpace. Key words :Power Distance,Collectivism/individualsm, Masculinity/feminimity, Uncertainty avoidance, deviant workpace behavior.